Immersive Remote UAV Application Platform: Factors and Requirements - Asechko, Maksym; Basarab, Oleksandr; Maksiuta, Dmytro; Cherkashyn, Serhii (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: to substantiate the concept of construction, develop software-algorithmic and hardware solutions that ensure increased accuracy, as well as to study the properties of an on-board navigation complex (OBC) of increased interference immunity based on the remote use of UAVs via a satellite data transmission system (NFRs). Methodology/approach: The methodological basis and research tool of this study are the methods for building models of dynamic systems, methods of statistical data processing, the theory of optimal evaluation and complex processing of navigation information, methods of simulation and semi-real-life modeling, as well as methods of full-scale testing. Originality/Relevance: The study conducted a comprehensive analysis of the effectiveness and limitations of the UAV remote control system via a satellite communication channel in the absence of an inertial navigation system (INS). A mathematical model was developed that allows estimating the maximum allowable time for remote use of the UAV without critical loss of controllability. Key findings: This study lays the foundation for the formation of measurable criteria for the effectiveness of UAV control in conditions of navigation data degradation, with an orientation towards practical implementation in combat, search and rescue or civilian high-risk conditions. Theoretical/methodological contributions: Systems analysis methods, network interaction theory, mathematical modeling methods, probability theory, machine learning methods, high-level programming theory, software testing methods.